The Role of Parental Parenting in the Formation of the Child’s Self-Concept - Azizah Rohmalimna; Olie Yeau; Puiry Sie (World Psychology, 2022)
Parents have an important role in the formation of self-concept in children. Children who receive positive treatment will have a positive self-concept and vice versa. Children who receive unpleasant treatment from their parents will have a negative self-concept. Parents are one of the main factors that can influence the formation of self-concept in a child. If the child erred, the parents directed the child, advised, and gave understanding so that the child could understand to correct his mistakes in an appropriate way. Positive self-concept arises from good self-qualities, no hesitation in acting, daring to try, and daring to make decisions. On the other hand, children who receive unpleasant treatment from parents, such as often getting naughty and stupid words when making a mistake, will appear a negative self-concept in children. Negative self-concept arises from the poor quality of self-adjustment, doubts in oneself, fear of trying and not daring to make decisions. This article aims to describe the role of parents in parenting until their self-concept is formed. The method used is a literature study. This paper is a form of view resulting from a literature study conducted by the author of books and journals related to the Role of Parenting in the Formation of Children’s Self-Concept. The results obtained from the studies carried out explain that parental parenting has an important role in shaping self-concept in children.